2008
DOI: 10.1210/jc.2007-1726
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Free Estradiol and Sex Hormone-Binding Globulin in Women with and without Premenstrual Dysphoric Disorder

Abstract: Luteal phase concentrations of free E2, percent free E2, and SHBG differ significantly between women with and without PMDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
1
21
1
2
Order By: Relevance
“…This latter finding is generally consistent with previous literature indicating that ovarian hormone levels, and those of many of their metabolites, do not differ in women with PMDD compared to healthy controls: Both lower (Thys-Jacobs et al 2008) and higher (Wang et al 1996) estradiol levels have been observed in women with menstrual-related mood disorders. Lower levels of progesterone have also been reported in women with PMS (Wang et al 1996), a finding not replicated by several previous and subsequent studies (Backstrom et al 1983; Eriksson et al 1992; Facchinetti et al 1993; Rubinow et al 1988; Thys-Jacobs et al 2008; Rapkin et al 1997). Different (Facchinetti et al 1993) and similar (Reame et al 1992) patterns of luteinizing hormone release have been reported in women with PMS compared to controls.…”
Section: Discussionsupporting
confidence: 92%
“…This latter finding is generally consistent with previous literature indicating that ovarian hormone levels, and those of many of their metabolites, do not differ in women with PMDD compared to healthy controls: Both lower (Thys-Jacobs et al 2008) and higher (Wang et al 1996) estradiol levels have been observed in women with menstrual-related mood disorders. Lower levels of progesterone have also been reported in women with PMS (Wang et al 1996), a finding not replicated by several previous and subsequent studies (Backstrom et al 1983; Eriksson et al 1992; Facchinetti et al 1993; Rubinow et al 1988; Thys-Jacobs et al 2008; Rapkin et al 1997). Different (Facchinetti et al 1993) and similar (Reame et al 1992) patterns of luteinizing hormone release have been reported in women with PMS compared to controls.…”
Section: Discussionsupporting
confidence: 92%
“…Undiagnosed polycystic ovary syndrome may have potentially affected the findings but this was unlikely given low serum T. We did exclude participants using hormonal contraceptives as those could raise SHBG. It is possible that analysis by exercise was affected by menstrual cycle phase, since SHBG rises in the luteal phase [Thys-Jacobs et al 2008] and more women in the exercise group were in the luteal phase. However, we would then expect to see significant differences by exercise group, which was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…Although the menstrual cycle hormonal profiles of women with PMS showed that the pregnanediol peak occurred significantly later in PMS patients than in asymptomatic females [4], the results of Salonia et al. indicate that sexual functions do not depend on hormonal changes during the cycle [31].…”
Section: Introductionmentioning
confidence: 94%